Optimization on oxidation process using 2K factorial design method - Yeap Li Chian (Universiti Malaysia Perlis, 2008)
Silicon technologies progress in the last twenty years has traced the path to the unprecedented revolution of information technologies, which has changed everybody’s lifestyles. With the help of software, the world of technology can be improve and get even better. In this project, design of experiments (DOE) is applied to oxidation process optimization. Oxidation process is one of the important processes in wafer fabrication. With different application required, different oxide thickness can be done. To give an accurate oxide thickness, DOE can help. This project study the concept of DOE in applies to oxidation process. The parameter of oxidation is studied and result validated on both practical and generated. With the 2K factorial design method, the experiments designed, conducted and analysis done for optimization. Result from experiment will be considering its pure error to obtain an optimum parameter. Finally, the oxidation process will be conduct using the optimum parameter. For this project, with 1054ºC, 35 minutes should built 4000Å oxide thickness but the real time experiment is getting 3700.5Å oxide thickness. From here, the different of practical result and theoretical result can be notified. The percentage error also calculated as about 8%. Generally, the real time experiment will not run too far from the theoretical. The small percentages error is due to the environment and human error problem when we conduct experiments. It is reasonable results because the optimum parameter generated by the software has been adjust to round number for easy experimentation.